Hitam-putih kurikulum 2013 / Zulfikri Anas dan Akhmad Supriyatna; Editor, Mujakir - ZULFIKRI Anas dan Akhmad Supriyatna; Editor, Mujakir; AKHMAD Supriyatna; MUJAKIR; 22570-PD/B.15 (AMP, 2014)
236 hlm. ; 20 cm.